2004
DOI: 10.2355/isijinternational.44.1157
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Model of Cored Wire Injection in Steel Melts

Abstract: Mathematical models for tracking the melting of cored wire during its injection into the steel bath have been developed in the past though important aspects of the formulations have not been discussed in sufficient detail. As a result, it is difficult to use the results of these models to derive benefits for a specific steel melting shop.A general purpose mathematical model has been developed at R & D, Tata Steel, using the finite difference approach with a fully implicit scheme to simulate the process of core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 6 publications
1
31
0
1
Order By: Relevance
“…In this situation, it is observed that the increased heat transfer coefficient of the bath reduces the frozen layer thickness and time taken in the first step for the plate [1], spherical [6] and cylindrical [3] additives. This prediction is implicit in [2,5] whereas in [4] only instant equilibrium temperature at the interface between the additive and the bath immediately after the immersion of the additive in the bath is found. Closed-form solutions for the growth of the maximum frozen layer thickness, its time of development and the total time of freezing and melting of the bath material onto the cylindrical additive in an agitated bath [7] is also reported recently.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this situation, it is observed that the increased heat transfer coefficient of the bath reduces the frozen layer thickness and time taken in the first step for the plate [1], spherical [6] and cylindrical [3] additives. This prediction is implicit in [2,5] whereas in [4] only instant equilibrium temperature at the interface between the additive and the bath immediately after the immersion of the additive in the bath is found. Closed-form solutions for the growth of the maximum frozen layer thickness, its time of development and the total time of freezing and melting of the bath material onto the cylindrical additive in an agitated bath [7] is also reported recently.…”
Section: Introductionmentioning
confidence: 94%
“…Investigation of such a situation that leads to thermal resistance of the frozen layer negligible with respect to that of the bath seldom appears in the literature. However, the occurrence of the first step for plate [1], cylindrical [2][3][4] and spherical [5,6] shaped solid additives is analyzed when the frozen layer formed on these additives has their thermal resistances comparable with those of their bath. In this situation, it is observed that the increased heat transfer coefficient of the bath reduces the frozen layer thickness and time taken in the first step for the plate [1], spherical [6] and cylindrical [3] additives.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to represent the same heat transfer phenomena by the following one dimensional unsteady state heat conduction equation. An earlier work 1) of this author had detailed the procedure. Equation (1) has been used for the present study and solved with the relevant initial and boundary conditions to determine 1. the temperature distribution inside the Al wire and the solidified shell, 2. the total time taken for the melting of the shell and Al wire.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The imperfect contact between the wire surface and this shell results in a thermal contact resistance (R T ) between the two. [1][2][3][4][5][8][9][10][11][12][13][14] These values for different metal combinations have been derived experimentally, [15][16] which vary from 1.9ϫ10 Ϫ4 to 9.1ϫ10 Ϫ4 m 2 s K/J. The authors have considered the value as 2.4ϫ10 Ϫ4 m 2 s K/J for the present study.…”
Section: Routes For Aluminium Wire Meltingmentioning
confidence: 99%
See 1 more Smart Citation